MEDIA PLAYER CONTROLLING BY HAND GESTURES USING OPENCV AND PYTHON - Ms. Vanita1 .D. Jathav , Ms. Kalyani2. P. Modak , Ms. Shraddha3 .S. Dhage , Ms. Prerana4. B. Shinde , Ms.Vaishnavi5. P. Bansode , Ms. Suchitra6 .R. Gavali . (International Journal of Innovations in Engineering Research and Technology, 2022)
In today’s world, everyone opts for fast interaction with complex systems that ensure a quick response. Thus, with increasing improvement in technology, response time and ease of operations are the concerns. Here is where human-computer interaction comes into play.In this Project we try to control our media player using hand gestures with the help of OpenCV and Python. . Hand gesture is an important component of body languages in linguistics. Human computer interaction becomes easy with the use of the hand as a device. Use of hand gestures to operate machines would make interaction interesting. Gesture recognition has gained a lot of importance. Hand gestures are used to control various applications like windows media player, robot control, gaming etc. Use of gesture makes interaction easy, convenient and does not require any extra device. Vision and audio recognition can be used together. But audio commands may not work in noisy environments.